2005
DOI: 10.1080/00218839.2005.11101138
|View full text |Cite
|
Sign up to set email alerts
|

Pollination of ‘criollo’ avocados (Persea americana)and the behaviour of associated bees in subtropical Mexico

Abstract: 2005) Pollination of 'criollo' avocados (Persea americana) and the behaviour of associated bees in subtropical Mexico, Journal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 10 publications
0
14
0
5
Order By: Relevance
“…Based on species abundance on the flowers, foraging behaviour, and number of pollen grains on the insect's body zones that came in contact with the avocado stigma, they concluded that eight to 10 species of stingless bees were effective pollinators of avocado, together with the Mexican honey wasp. Can-Alonso et al (2005), working in commercial orchards, found that A. mellifera and Trigona nigra carried comparable amounts of avocado pollen grains on their bodies, but that this number was significantly less on Nannotrigona perilampoides. They too concluded that native stingless bees are potentially efficient pollinators of this crop.…”
Section: Coffea Canephoramentioning
confidence: 99%
“…Based on species abundance on the flowers, foraging behaviour, and number of pollen grains on the insect's body zones that came in contact with the avocado stigma, they concluded that eight to 10 species of stingless bees were effective pollinators of avocado, together with the Mexican honey wasp. Can-Alonso et al (2005), working in commercial orchards, found that A. mellifera and Trigona nigra carried comparable amounts of avocado pollen grains on their bodies, but that this number was significantly less on Nannotrigona perilampoides. They too concluded that native stingless bees are potentially efficient pollinators of this crop.…”
Section: Coffea Canephoramentioning
confidence: 99%
“…en aguacate, para la variedad Hass, se ha encontrado que un árbol puede llegar a producir hasta 2 millones de flores, más de mil veces la cantidad de frutos que puede soportar, pero se ha estimado que únicamente llegan a cuajado entre el 0,001% y 0,1% (Whiley et al, 1988;Dixon y sher, 2002;Can-Alonzo et al, 2005;Cossio-Vargas et al, 2007;scora et al, 2007).…”
Section: Research Advances On the Productive Behavior Of Avocado Treeunclassified
“…The stingless bees (Hymenoptera, Apidae, Meliponini) are diverse group of eusocial, corbiculate bees, with around 500 species distributed in the tropical and southern subtropical regions of the world [42], with potential to be used as commercial pollinators [43,44,45,46]. In the Neotropics, the stingless bee Melipona eburnea is an important flower pollinator of Andean plants [47].…”
Section: Introductionmentioning
confidence: 99%